DISSIMILAR WELDING BETWEEN AUSTENITIC AND A LEAN UPLEX STAINLESS STEEL (Journal of Industrial and Mechanical Engineering, 2021)
In recent years, materials science has worked hard to develop materials with specific chemical compositions, microstructures, and properties.Due to optimization issues in their selection, today, the industry is challenged to achieve sound welds between dissimilar materials. These welds are known as dissimilar welds.The objective of this work is to study the microstructural evolution and the mechanical behavior of dissimilar welds between austenitic and lean duplex stainless steel.For this purpose, a coupon was welded where a chemical and microstructural characterization was carried out, hardness scans and the tensile properties were determined.The mechanical results obtained show a decrease in hardness in the heat affected zone of austenitic steel, a preferential breaking zone in tensile tests.
Keywords: Pulsed Arc; Dissimilar Welding; Metallurgical Characterization; Mechanical Characterization